2014
DOI: 10.1002/wat2.1018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risks posed by mixtures of chemicals in freshwater environments: case study of Lake Geneva, Switzerland

Abstract: Aquatic organisms are typically exposed simultaneously to several organic compounds released from human activities like agriculture, industries, or simply from people living in cities. The ecological risk assessment of mixtures of such compounds has therefore to be addressed by scientists. The aims of this paper are (1) to describe the current mixture risk assessment procedures, (2) to apply such approach to a specific case study, Lake Geneva and the River Rhône in Switzerland, and (3) to discuss the outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 82 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…Naturally, aquatic organisms are exposed simultaneously to several organic and inorganic compounds resulting from human agricultural, industrial and domestic activities [37]. In this study, SDS modulated the toxicity of the heavy metals and vice versa, giving EC 50S higher (lower toxicities) than those of the individual heavy metals but lower than that of SDS, in all the ternary mixtures tested.…”
Section: Discussionmentioning
confidence: 70%
“…Naturally, aquatic organisms are exposed simultaneously to several organic and inorganic compounds resulting from human agricultural, industrial and domestic activities [37]. In this study, SDS modulated the toxicity of the heavy metals and vice versa, giving EC 50S higher (lower toxicities) than those of the individual heavy metals but lower than that of SDS, in all the ternary mixtures tested.…”
Section: Discussionmentioning
confidence: 70%
“…Even when more data are available, allowing the use of statistical extrapolation techniques, based on SSDs, the specificity of the mode of action of the substance should be a priority factor in calculating the ecological risk (Guérit et al, 2008). Several studies have documented the intuitive approach that the effect of whole mixtures will be higher than the effects of a single individual compound with different species and different classes of chemicals, in the laboratory, in mesocosms, and in the field (Gregorio and Chèvre, 2014). In addition, intraspecific and interspecific competition is rarely considered when extrapolating from lower to higher biological organization levels (Kattwinkel and Liess, 2014 and literature quoted therein).…”
Section: Discussionmentioning
confidence: 99%
“…The proposal for new standards by DETEC is part of this dynamic. Since the early 2000s, several studies have focused on the impacts of mixtures of pesticide on environmental species (see e.g., Backhaus et al, 2003;Beyer et al, 2014;Gregorio & Chèvre, 2014;Laetz et al, 2009;Relyea, 2009;Rizzati, Briand, Guillou, & Gamet-Payrastre, L., 2016). These studies showed that pesticides can act in isolation, as currently accounted for in the evaluation of the chemical status (Wittmer, Junghans, et al, 2014b), but can also interact in dose additive or synergic ways.…”
Section: Mixture Of Pesticides Must Be Taken Into Accountmentioning
confidence: 99%